Online Learning Readiness among Higher Institution Students during Covid-19 Pandemic - Abu Bakar, Mohd Bakri; Izni Zamri, Fatin Nor; Ezetty Rohaizat, Nur Izwani (Selangor Humaniora Review, 2021)
Online learning has become a new norm to the education system because the traditional classes have to be postponed from early childhood to tertiary levels due to the Covid-19 pandemic. Online learning platforms are being used widely worldwide to ensure students are not left behind. This study investigates the online learning readiness among higher institution students in Selangor during the Covid-19 pandemic. The research design of this study is descriptive, which uses a quantitative method by distributing a set of 3-point Likert scale questionnaires using Google Forms. It consists of two parts: Online Learning Readiness and Relationship Between Readiness and Performance. The first part consists of six dimensions: expectations, self-direction, learning preferences, self-study habits, technology skills, and hardware/software skills, while the second part includes six questions. 120 higher institution students, which are 93 female students and 27 male students, were involved in this study as the respondents. The findings revealed that the majority of the respondents shared positive responses regarding online learning readiness and also a positive relationship between online learning readiness and performance. This shows that the respondents are ready to participate in online learning during the Covid-19 pandemic. Keywords: Covid-19 Pandemic, Online Learning Readiness, Open Distance Learning, Performance